Numbers, diet and feeding methods of Common Shelduck Tadorna tadorna wintering in the estuarine bays of Aiguillon and Marennes-Ol - Viain, Anouck; Corre, Frédéric; Delaporte, Philippe; Joyeux, Emmanuel; Bocher, Pierrick (Wildfowl, 2013)
Common Shelduck Tadorna tadorna were studied in western France, at two wintering sites of international importance for this species. The numbers, densities, feeding activity, feeding methods and diet of Shelduck feeding in the soft sediments of Aiguillon Bay and Marennes-Oléron Bay, on the Charente-Maritime and South Vendée coast, were examined. The birds spent 60% of their time feeding. Prey were obtained mainly by Shelduck moving their bills in a scything action through the mud and sieving small organisms < 8.0 mm long from the upper two centimetres of the surface. Faecal analysis indicated that the diet was composed mainly of small invertebrates, primarily the mudsnail Hydrobia ulvae. However, the presence of plants and other invertebrates in the diet indicated that they also exploited food resources in adjacent saltmarshes.